2016
DOI: 10.3847/0004-637x/816/2/97
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Considerations for Life in Multi-Habitable Planetary Systems

Abstract: Inspired by the close-proximity pair of planets in the Kepler-36 system, we consider two effects that may have important ramifications for the development of life in similar systems where a pair of planets may reside entirely in the habitable zone of the hosting star. Specifically, we run numerical simulations to determine whether strong, resonant (or non-resonant) planet-planet interactions can cause large variations in planet obliquity-thereby inducing large variations in climate. We also determine whether o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 55 publications
3
3
0
Order By: Relevance
“…Many of these aspects can only be studied through detailed numerical models, which fall outside the scope of this work. Despite these simplifications, our conclusions are in agreement with recent numerical simulations [17] which had incorporated most of the aforementioned factors.…”
Section: Lithopanspermia -A Simple Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…Many of these aspects can only be studied through detailed numerical models, which fall outside the scope of this work. Despite these simplifications, our conclusions are in agreement with recent numerical simulations [17] which had incorporated most of the aforementioned factors.…”
Section: Lithopanspermia -A Simple Modelsupporting
confidence: 91%
“…As a result, the fraction of rocks that are transferred between planets would be comparable to (although smaller than) the fraction of rocks that fall back on the surface of the originating planet. 1 This conclusion is fully consistent with the previous numerical simulations undertaken by Steffen and Li [17]. Thus, the TRAPPIST-1 system is expected to be more efficient than the Earth-to-Mars case in facilitating panspermia.…”
Section: Lithopanspermia -A Simple Modelsupporting
confidence: 88%
“…In our Solar System, transit times of impact ejecta between terrestrial planets are found to be 10 6−7 yr in numerical simulations (e.g., Gladman et al 1996;Worth et al 2013), consistent with cosmic-ray exposure times reported for Martian meteorites found on Earth (Eugster et al 2006). Transit times may be much shorter in other planetary systems, where different orbital architectures result in very different dynamical evolution of ejected debris (Steffen & Li 2016). The recently discovered TRAPPIST-1 system is particularly intriguing in this regard, as it consists of seven, nearly Earth-massed planets orbiting an M-type dwarf star.…”
Section: Introductionsupporting
confidence: 84%
“…Transit times may be much shorter in other planetary systems, where different orbital architectures result in very different dynamical evolution of ejected debris (Steffen & Li 2016). The recently discovered TRAPPIST-1 system is particularly intriguing in this regard, as it consists of seven, nearly Earth-massed planets orbiting an M-type dwarf star.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, planets may have formed outside the HZ and escaped the brunt of the long and intense pre-main-sequence phase of M-dwarfs, before eventually migrating inwards into the HZ at a later stage; see Tamayo et al (2017) and Ormel et al (2017). Finally, M-dwarf planetary systems might possess inherent advantages such as the enhanced transport of life between planets via lithopanspermia by several orders of magnitude compared to the Earth-Mars system (Steffen and Li, 2016;Lingam and Loeb, 2017c;Krijt et al, 2017). However, in each of the above instances, either a high degree of fine tuning might be required or the feasibility of the proposed mechanisms remains indeterminate.…”
Section: Discussionmentioning
confidence: 99%